Supplementation of Brown Seaweed (Turbinaria conoids) Powder and its Effect on Blood Metabolites and Mineral Profile in Adult Goats - Yengkhom, Rojita; Singh, Putan; Muwel, Nirmala; Raje, Kanti; Handique, Bornalee; Venkatswaran, K (Indian Journal of Animal Nutrition, 2019)
Â The study was conducted to examine the effects of brown seaweed supplementation on blood biochemical parameters and serum mineral profile in adult goats. Fifteen adult goats were assigned to 3 treatments (CON, T1 and T2) based on the CRD. Goats in CON group were fed a standard ration with no seaweed supplement; however, goats in T1 and T2 groups were given concentrate mixture having 4% and 8% of brown seaweed, respectively. PCV, Hb, albumin, globulin and A:G did not differ significantly among the groups, however, serum glucose level was significantly higher in T2 followed by T1 and CON and total protein level was significantly higher in T2 as compared to T1 and CON. Serum mineral parameters like Ca, P, Fe, and Mn did not differ significantly among the groups whereas Cu level was found to be higher in T1 as compared to CON and T2 and serum Zn concentration was significantly higher in T1 followed by T2 and CON. It was concluded that incorporation of brown seaweed (2% and 4%) increased serum metabolites like glucose, protein and serum minerals like Cu, Zn without any adverse impact on other blood metabolites and thus vital organ functions.